Factors Affecting Quality of Life in Hypertensive Patients: A Cross-Sectional Study in Hue, Vietnam - Thi Han Ny, Dang; An, Le Van; Thanh Hai, La; Van Quan, Pham (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Hypertension is a common chronic condition that leads to serious complications and negatively affects patients’ quality of life (QoL). Therefore, improving hypertension management and understanding factors that influence QoL has become an important goal in patient care. However, in Hue, Vietnam, no research has been conducted to evaluate how sociodemographic factors affect the QoL of hypertensive patients.Purpose: This study aimed to evaluate the sociodemographic factors influencing the quality of life of hypertensive patients in Hue, Vietnam.Methods: This cross-sectional study was conducted among 172 hypertensive patients receiving treatment at the Internal Medicine Department in Hue, Vietnam. Given the limited timeframe and research resources, convenience sampling was employed to facilitate rapid and effective participant recruitment. Descriptive statistics were used to examine the mean quality of life (QoL) scores, which were assessed using the WHOQOL-BREF scale. Independent t-tests and ANOVA were performed to analyze differences in QoL across sociodemographic factors within the four WHOQOL-BREF domains: physical health, psychological health, social relationships, and environmental health. Linear regression analysis was applied to identify associations between QoL domains and the independent variables.Results: The results showed that 93.6% of patients had a moderate level of QoL. Multivariate linear regression analysis revealed that age, economic status, and physical activity were positively associated with three QoL domains: physical, psychological, and environmental health. However, place of residence was negatively associated with the environmental domain (95% CI = -5.64, -0.97), and the presence of comorbidity was negatively associated with three domains: physical health (95% CI = -7.76, -2.00), psychological health (95% CI = -6.47, -0.64), and environmental health (95% CI = -4.84, -0.07).Conclusion: The findings of this study suggest that younger age, a moderate to high economic status, and engagement in regular physical activity are positively associated with higher QoL scores. Conversely, residing in rural areas and having comorbid conditions are negatively associated with QoL. These results underscore the need for targeted and context-specific interventions aimed at enhancing the quality of life in individuals living with hypertension.